Identification and characterization of new structural scaffolds modulating the activity of Mycobacterium tuberculosis dihydroneopterin aldolase (FolB) in vitro - Falcão, Virginia Carla de Almeida; Czeczot, Alexia de Matos; Alam, Mohammad Maqusood; Park, Kyu-Ho Paul; Heo, Jinyeong; Woo, Minjeong; Camini, Ana Micaela; Timmers, Luis Fernando Saraiva Macedo; Shum, David; Perelló, Marcia Alberton; Basso, Luiz Augusto; Machado, Pablo; et al. (Frontiers in Tropical Diseases, 2024)
IntroductionAntifolates were among the first broad-spectrum compounds used as antimycobacterial agents and can still be of use when no other therapeutic options are available. The discovery of compounds targeting the essential folate synthesis pathway could lead to new therapeutic agents to treat tuberculosis (TB). In particular, the enzyme required for the conversion of 7,8-dihydroneopterin (DHNP) to 6-hydroxymethyl-7,8-dihydropterin (HP) and glycolaldehyde (GA) in the folate pathway (MtbFolB, a dihydroneopterin aldolase - DHNA, EC 4.1.2.25), has received little attention as a potential drug target so far, as it is acting upstream of the clinically validated targets dihydropteroate synthase (DHPS; EC 2.5.1.15) and dihydrofolate reductase (DHFR; EC 1.5.1.3).MethodsWe conducted a small-scale diversity screening to identify MtbFolB inhibitors using a microplate-based enzyme inhibition assay. A total of 6,074 compounds were assembled, tested and confirmed in dose-response studies. A preliminary structure activity analysis was performed for the validated hit compounds, along with kinetic inhibition, time-dependent inhibition, as well as docking studies. ResultsThe screening resulted in the selection of 19 hits spanning 5 independent clusters. Dose-response studies of re-synthesized hits and newly synthesized derivatives displayed compounds with IC50 values ranging from 2.6 to 47 µM. The structure activity analysis revealed that bi-sulfonamide compounds could be explored for further optimizations. Docking studies highlighted two modes of binding for pyrazol-3-one compounds and, for the sulfonamide series, indicated several interactions with the catalytic Tyrosine-54 (Tyr54D) and Lysine-99 (Lys99A) residues of MtbFolB. DiscussionThrough this work, we established that the MtbFolB assay was able to select small molecules with inhibitory activities, opening prospects for larger scale screening. The sulfonamide compound 13 was also identified as the first compound directed against MtbFolB with an antimycobacterial activity.